1993
DOI: 10.1159/000187484
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prednisone on Renal Function in Man

Abstract: To clarify the rise in plasma creatinine concentration previously observed during prednisone treatment, we studied changes in renal function in Graves’ ophthalmopathy patients before and after 2 weeks of either prednisone 60 mg/day or retrobulbar radiotherapy (controls). Compared to retrobulbar radiotherapy, prednisone treatment was associated with an increase in: (a) plasma creatinine concentration (from 68 ± 4 to 76 ± 4 μmol/l), (b) glomerular filtration rate (GFR, from 93 ± 4 to 102 ± 5 ml/min/1.73 m2<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…Aloxiprin, in a dose equivalent to about 4 g salicylate, caused an average decrease of 25% in creatinine clearance and a 38% increase in plasma creatinine. GFR measured by 51 Cr-EDTA clearance remained unchanged. The authors suggested that salicylates could either disturb creatinine binding to serum proteins or competitively inhibit tubular secretion of creatinine.…”
Section: Salicylatesmentioning
confidence: 90%
See 2 more Smart Citations
“…Aloxiprin, in a dose equivalent to about 4 g salicylate, caused an average decrease of 25% in creatinine clearance and a 38% increase in plasma creatinine. GFR measured by 51 Cr-EDTA clearance remained unchanged. The authors suggested that salicylates could either disturb creatinine binding to serum proteins or competitively inhibit tubular secretion of creatinine.…”
Section: Salicylatesmentioning
confidence: 90%
“…This was explained as being a result of a reduction of urinary creatinine excretion and accumulation of plasma creatinine until a new steady state had been reached [14]. However, no concomitant changes in GFR were detected when measured by inulin [11,12], 125 I-iothalamate [13] or 51 Cr-EDTA clearances [14]. No effects of cimetidine on the assay procedure for creatinine were observed [9,12].…”
Section: Cimetidinementioning
confidence: 99%
See 1 more Smart Citation
“…Corticosteroides have been reported to increase GFR nonspecifically [6] but nevertheless the creatinine concentration increased by 10% [7]. This increase in creatinine is attributed to the catabolic state with protein degeneration and loss of muscle tissue induced by the steroid treatment [2].…”
Section: Exogenous Substancesmentioning
confidence: 99%
“…Glucocorticoid therapy has been reported to be associated with increased GFR, and paradoxically, increased creatinine and cystatin C concentrations [22,23,37]. While glucocorticoid therapy is not known to affect gentamicin clearance [38], an increase in GFR associated with such …”
Section: Figurementioning
confidence: 99%